Da'wah Patterns in Developing Religious Harmony in Semarang City - Siti Prihatiningtyas; Siti Solihati; Lukmanul Hakim (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study aims to find the format of the pattern of developing religious harmony and the role of government and religious leaders in creating a conducive situation in Semarang. The research uses a qualitative approach. Data were collected through observation, interview, and documentation techniques. The results of this study indicate that the city of Semarang consists of various tribes, religions, and ethnicities, the people have a high sense of tolerance. This is due to the community's spiritual condition and the mindset of an advanced society due to many universities. Communication and cooperation are well established between government figures, religious leaders, and community leaders in various community harmony forums and organizations such as Petamas and FKUB. The forum can be used as a medium for dialogue. From the researcher's analysis, harmonization in religious harmony is influenced by activities that create and touch a sense of togetherness and affection. The pattern of social da'wah is an alternative in building tolerance and harmonization over the plurality of society.